Magnetic resonance evidence of hypoxia in a homozygous alpha-knockout of a transgenic mouse model for sickle cell disease. - Fabry, M E (1996)
All transgenic mouse models for sickle cell disease express residual levels of mouse globins which complicate the interpretation of experimental results. We now report on a mouse expressing high levels of human betaS and 100% human alpha-globin. These mice were created by breeding the alpha-knockout and the mouse beta(major)-deletion to homozygosity in mice expressing human alpha- and betaS-transgenes. These betaS-alpha-knockout mice have accelerated red cell destruction, altered hematological indices, ongoing organ damage, and pathology under ambient conditions which are comparable with those found in alphaH betaS-Ant[betaMDD] mice without introduction of additional mutations which convert betaS into a "super-betaS" such as the doubly mutated betaS-Antilles. This is of particular importance for testing strategies for gene therapy of sickle cell disease. Spin echo magnetic resonance imaging at room air and 100% oxygen demonstrated the presence of blood hypoxia (high levels of deoxygenated hemoglobin) in the liver and kidneys that was absent in control mice. We demonstrate here that transgenic mice can be useful to test new noninvasive diagnostic procedures, since the magnetic resonance imaging technique described here potentially can be applied to patients with sickle cell disease.